Dance Dramaturgy Modes of Agency, Awareness and Engagement - Hansen, Pil.; Hansen, Pil.; Callison, Darcey.; Callison, Darcey. (New World Choreographies,, 2015)
Ten international dramaturg-scholars advance proposals that reset notions of agency in contemporary dance creation. Dramaturgy becomes driven by artistic inquiry, distributed among collaborating artists, embedded in improvisation tasks, or weaved through audience engagement, and the dramaturg becomes a facilitator of dramaturgical awareness.